Model‐informed drug repurposing: A pharmacometric approach to novel pathogen preparedness, response and retrospection. Issue 9 (23rd February 2021) - Dodds, Michael; Xiong, Yuan; Mouksassi, Samer; Kirkpatrick, Carl M.; Hui, Katrina; Doyle, Eileen; Patel, Kashyap; Cox, Eugène; Wesche, David; Brown, Fran; Rayner, Craig R.
Abstract : During a pandemic caused by a novel pathogen (NP), drug repurposing offers the potential of a rapid treatment response via a repurposed drug (RD) while more targeted treatments are developed. Five steps of model‐informed drug repurposing (MIDR) are discussed: (i) utilize RD product label and in vitro NP data to determine initial proof of potential, (ii) optimize potential posology using clinical pharmacokinetics (PK) considering both efficacy and safety, (iii) link events in the viral life cycle to RD PK, (iv) link RD PK to clinical and virologic outcomes, and optimize clinical trial design, and (v) assess RD treatment effects from trials using model‐based meta‐analysis. Activities which fall under these five steps are categorized into three stages: what can be accomplished prior to an NP emergence (preparatory stage), during the NP pandemic (responsive stage) and once the crisis has subsided (retrospective stage). MIDR allows for extraction of a greater amount of information from emerging data and integration of disparate data into actionable insight.